Health promotion integrated into school policy and practice : experiences from the implementation of the Norwegian network of health promoting schools - Samdal, Oddrun (2012)
This paper aims to identify prerequisites for successful implementation of the health promoting school principles as identified in the Norwegian network of Health promoting schools. The analysis is based on project documents and interviews with teachers and principals. The findings highlighted the following core dimensions in the implementation process: systematic approach taken to planning and implementing the project, active leadership balancing top-down and bottom-up processes as well as providing resources and adequate structures for time management, building on previous practice and competence to ensure familiarity and adequate level of demanded change, stimulation of teachers' motivation, collaboration with relevant partners and exchange of experiences with other schools in the national network, and the integration of the health promoting school initiative and activities in school policy documents ensuring that approaches run independently of single teachers. These elements have also been identified as vital for the sustainability of the health promoting initiative at the schools participating in the Norwegian network of health promoting schools. (Oddrun Samdal, Nina Grieg Viig, Bente Wold)